1991
DOI: 10.1093/arclin/6.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of brain impairment with the rey auditory verbal learning test: A comparison with other neuropsychological measures

Abstract: In this study the effectiveness of The Rey Auditory Verbal Learning Test (AVLT) at assessing patients with mixed brain impairment was compared with that of a number of other commonly used neuropsychological measures. Subjects were 50 patients with a mixture of medically confirmed neuropathologies, and 50 controls with no evidence of neurological history. Groups were equated for age, education, and sex. The AVLT was administered as pan of a full neuropsychological battery. Results indicated that all seven AVLT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The tests assessed a number of cognitive domains known to be affected by cardiac surgery. 17,18 The test battery consisted of the Rey Auditory Verbal Learning Test, 19 Rey Complex Figure Test, 20 Controlled Oral Word Association Test, 21 Symbol Digits Modalities Test, 22 Trail Making Tests A and B, 23 and Grooved Pegboard Test. 24 Other patient and perioperative characteristics were abstracted from the electronic health record by trained research staff.…”
Section: Neuropsychologic Testing and Other Patient And Perioperative...mentioning
confidence: 99%
“…The tests assessed a number of cognitive domains known to be affected by cardiac surgery. 17,18 The test battery consisted of the Rey Auditory Verbal Learning Test, 19 Rey Complex Figure Test, 20 Controlled Oral Word Association Test, 21 Symbol Digits Modalities Test, 22 Trail Making Tests A and B, 23 and Grooved Pegboard Test. 24 Other patient and perioperative characteristics were abstracted from the electronic health record by trained research staff.…”
Section: Neuropsychologic Testing and Other Patient And Perioperative...mentioning
confidence: 99%
“…Both show varying degrees of sensitivity to the presence of a variety of clinical disorders (Wechsler, 2009). The AVLT words recalled on Trial 5 provided the single best score in a comprehensive battery of tests, including the HRB, for discriminating between a group of patients with brain dysfunction and normal controls (Powell, Cripe, & Dodrill, 1991). Loring et al (2008) found a Cohen's d of 0.47 associated with AVLT differences between patients with left and right temporal lobe epilepsy, which was significantly larger than the value of 0.29 for discriminating between patients with left and right temporal lobe epilepsy on the basis of their California Verbal Learning Test scores.…”
Section: Selecting the Appropriate Test Batterymentioning
confidence: 99%
“…The tests assessed a number of cognitive domains known to be associated with vascular disease and thus potentially affected in individuals after cardiac surgery. [10][11][12] The testing battery consisted of the Rey Auditory Verbal Learning Test (RAVLT), 13 Delirium was assessed using a validated chart-review method. 19 Because clinical judgment was required, a research assistant who one of the authors (KN, a psychiatrist) trained in formal delirium assessment performed all the chart abstractions using a chart-based instrument.…”
Section: Olfaction Testingmentioning
confidence: 99%